BETWEEN NATURE (FITRAH) AND SOCIAL CONSTRUCTION: FELIX SIAUW’S GENDER THOUGHT IN THE BOOK WANITA BERKARIR SURGA - Salma Sabila Dieni (Department Islamic Education, Faculty of Education and Teacher Traning, Universitas Islam Bandung, 2026)
Gender issues in Islam remain a complex and contested discourse, encompassing theological, social, and structural dimensions. This study analyzes Felix Siauw’s gender perspective in Wanita Berkarir Surga by engaging it in critical dialogue with modern gender theory, particularly in relation to the tension between fitrah-based and constructivist approaches. It also examines the relevance of this perspective in the context of contemporary Muslim women’s lives. This research employs a qualitative library research method, using the book as the primary source and supported by literature on feminism, gender sociology, and contemporary Islamic studies. Data are analyzed through content analysis. The findings show that Siauw’s perspective is grounded in the concepts of fitrah and complementarity, where gender differences are viewed as natural and mutually supportive. Male leadership is framed as responsibility, while women’s domestic roles are elevated as central to family and civilizational development. However, gender-insensitive mosque structures are found to limit women’s participation, reflecting patriarchal social constructions. Critically, although the perspective offers strong theological grounding, it requires contextual reinterpretation to remain relevant and to avoid reinforcing limitations on women’s roles in contemporary society.